Innovation of Benalu Jeruk Leaf Antioxidant Biscuits with a Combination of Sweet Potato Leaf in the Gen-Z Era - Udayani, Ni Nyoman Wahyu; Wulandari, Ni Kadek Ganis; Meika, Ni Putu Trisna; Putri, Ni Komang Ary Agustina Berliana (International Journal of Health Sciences, 2024)
Free radicals are toxic by-products of aerobic metabolism and can cause oxidative damage and tissue dysfunction. Antioxidants can play a role in overcoming excess free radicals in the body by capturing free radicals and preventing chain reactions. Orange bitter melon leaves and sweet potato leaves are considered to contain flavonoids and anthocyanins that act as antioxidants. Therefore, a biscuit innovation was made with orange and sweet potato benalu leaf powder with antioxidants. This study aimed to determine the antioxidant content of biscuits with a combination of orange and sweet potato leaf powder. The biscuits were tested for water content and hedonic and antioxidant activity test using the DPPH method. The antioxidant test results showed that the IC50 value was 179.753, with a moisture content value of 2.21%. Hedonic test results show that the most preferred taste is in F1 because the use of the right simplisia powder ratio can provide an alluring taste. Things that must be considered from this study are that further experiments need to be carried out regarding the effect of giving biscuits containing antioxidants.